Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Motivasi Belajar dan Hasil Belajar Biologi Siswa Kelas XI IPA SMA Negeri 18 Bulukumba - Irham Irham; Yusminah Hala; Alimuddin Ali (UNM Journal of Biological Education, 2017)
This study is quasy experiment research, which aims at examining (1) learning motivation of grade XI IPA students at SMAN 18 Bulukumba taught by using cooperative learning model of Jigsaw type, (2) the learning outcomes of grade IPA student at SMAN 18 Bulukumba taught by using cooperative learning model of Jigsaw type, (3) the influence of cooperative learning model of Jigsaw type toward learning motivation of grade IPA student at SMAN 18 Bulukumba, (4) the influence of cooperative learning model of Jigsaw type toward learning outcomes of grade IPA student at SMAN 18 Bulukumba. The population of the study the entire students of grade XI IPA of the second semester at SMAN 18 Bulukumba of academic year 2015/2016. The sample of the study are students of grade XI IPA2 and grade XI IPA3 with the total of 61 students. Samples were chosen by employing simple random sampling technique. Data was obtained by using quetionnaire of learning motivation and test of learning outcomes. The results of the study revealed were (1) student’s learning motivation in the control class after the treatment is 90.90 and is in very high categories; (2) ) student’s learning in the experiment class after the treatment is 104.16 and is in very high categories; (3) the students learning outcomes of Biology subject in the control class after the treatment is 74.24 and is in very high categories; (4) the students learning outcomes of Biology subject in the experiment class after the treatment is 83.84and is in very high categories; (5) the implementasi of cooperative learning model of Jigsaw type give positive influence toward learning and learning outcomes of grade XI IPA students at SMAN 18 Bulukumba.